Early Growth Response of Kalantas (Toona calantas Merr. & Rolfe) to Different Potting Media and Biostimulant Application - Cotillon, Josephine (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigates the early growth response of Toona calantas (Kalantas) to Different Potting Media and Biostimulant Application in Ilocos Sur, Philippines. A two-factor completely randomized design tested the effects of three soil media types and varying biostimulant doses on seedling growth. Results showed that forest soil with carbonized rice hull combined with a full dose of biostimulant significantly improved height, diameter, root-shoot ratio, and survival rate. The findings emphasize the importance of using forest soil compositions and organic inputs in optimizing the propagation of T. calantas. This study provides practical guidelines for conservation and reforestation initiatives involving threatened native species in similar ecological zones.
Keywords: Contextualization; Araling Panlipunan; Teaching Practices